Changes in lifestyle behaviors during the COVID-19 pandemic in children and adolescents with congenital heart disease - Honicky, Michele; Cardoso, Silvia Meyer; Lima, Luiz Rodrigo Augustemak de; Souza, Juliana Nicolodi; Vieira, Francilene Gracieli Kunradi; Back, Isabela de Carlos; Moreno, Yara Maria Franco (Sociedade de Pediatria de São Paulo, 2023)
Abstract Objective: To describe the changes in lifestyle behaviors during the COVID-19 pandemic in children and adolescents with congenital heart disease and to investigate the association of congenital heart disease complexity with lifestyle behavior changes. Methods: Cross-sectional study with 127 children and adolescents with congenital heart disease, who underwent cardiac procedure (mean postoperative time: 10.11±3.13 years), conducted between December 2020 and January 2021. Lifestyle behaviors, such as dietary intake, physical activity, sedentary behavior, and sleep, were assessed through telephone interview based on validated questionnaires. Dietary patterns were identified using principal component analysis. Frequency of general and specific combinations of healthy and unhealthy lifestyle behavior changes was evaluated. Multinomial logistic regressions were used to test the association between congenital heart disease complexity and changes in lifestyle behavior. Results: The main lifestyle behaviors acquired during pandemic were: 83.5% decreased physical activity; 37.0% increased sedentary behavior; 26.0% slept more than usual; and 23.6% adopted a less-healthy dietary pattern. Almost half of the participants (41.8%) had at least one unhealthy change in lifestyle behavior. Complex congenital heart diseases were associated with increased sedentary behavior (OR 3.49, 95%CI 1.23–9.90). Conclusions: Children and adolescents with congenital heart disease had unhealthy lifestyle behavior during the pandemic, mainly in the form of reduced physical activity and increased sedentary behavior.